1991
DOI: 10.1128/mcb.11.8.4088
|View full text |Cite
|
Sign up to set email alerts
|

Structure and transforming potential of the human cot oncogene encoding a putative protein kinase.

Abstract: A new transforming gene has been molecularly cloned from hamster SHOK cells transformed with DNA extracted from a human thyroid carcinoma cell line and named the cot (cancer Osaka thyroid) oncogene. cDNA sequencing disclosed that this oncogene codes for a protein with 415 amino acid residues, and computer matching showed 42 to 48% similarity matches with serine protein kinases. Its gene product was identified as a 52-kDa protein by transcription and translation in vitro. Expression of cot cDNA under transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 39 publications
(28 reference statements)
1
87
0
Order By: Relevance
“…Provirus insertion occurs between exon 7 and exon 8 giving rise to a protein with truncated carboxy-terminus. The truncated protein is highly oncogenic when overexpressed in the thymus of transgenic animals inducing thymomas (Ceci et al, 1997) and morphological transformation in SHOK and NIH3T3 cells (Miyoshi et al, 1991). It is expressed in most tissues but at relatively low levels, including ovarian and mammary tissues (Ohara et al, 1995;Erny et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provirus insertion occurs between exon 7 and exon 8 giving rise to a protein with truncated carboxy-terminus. The truncated protein is highly oncogenic when overexpressed in the thymus of transgenic animals inducing thymomas (Ceci et al, 1997) and morphological transformation in SHOK and NIH3T3 cells (Miyoshi et al, 1991). It is expressed in most tissues but at relatively low levels, including ovarian and mammary tissues (Ohara et al, 1995;Erny et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in most tissues but at relatively low levels, including ovarian and mammary tissues (Ohara et al, 1995;Erny et al, 1996). The human Tpl-2 homologue, known as Cot, was initially cloned by transfection of cDNA derived from the thyroid tumour cell line TCO-4 into the hamster cell line SHOK (Miyoshi et al, 1991). In situ hybridization histochemistry in a series of cell lines and tumour tissues revealed that Tpl-2/cot was overexpressed in parotid gland, gastric and colonic gland tumours as well as in the colon adenocarcinoma cell lines SW40 and WiDr (Ohara et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The serine/threonine kinase Cot was originally cloned from embryonic SHOK cells transformed with DNA extracted from a human thyroid carcinoma cell line (Miyoshi et al, 1991). The cot gene has su ered a gene rearrangement within the last coding exon of the cot proto-oncogene during this procedure (Miyoshi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The cot gene has su ered a gene rearrangement within the last coding exon of the cot proto-oncogene during this procedure (Miyoshi et al, 1991). The ®rst 397 amino acids of the Cot protein are identical to the oncogenic Cot (CotDC), whereas the 70 carboxyterminal amino acids are replaced by 17 completely di erent ones (Aoki et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation